Effects of Ice Freeze-Thaw Processes on U Isotope Compositions in Saline Lakes and Their Potential Environmental Implications - Zhang, Pu; Cao, Chenyang; Li, Xiangzhong; Pei, Xuezheng; Chen, Chi; Liang, Lihua; Ning, Youfeng; Tan, Liangcheng; Edwards, R. Lawrence (Frontiers in Earth Science, 2021)
The dissolved uranium (U) content in the water column of saline lakes varies little between ice-free seasons throughout the whole water column. Such uniformity allows for the potential absolute dating and/or paleohydrologic interpretations of lake sediments and biogenic shell materials using U isotopes. Before using these methods in cold regions, however, it is necessary to evaluate the effects that ice freeze-thaw processes have on the distribution of U isotopes in saline lake waters, and to determine the amount of variation in U isotopic values when such processes occur. In this paper, we collected ice and dissolved water samples from six lakes with variable salinity in February 2021. Five groundwater and three water samples from rivers into Qinghai Lake were sampled in November 2020. The sampled water was analyzed for dissolved concentrations of 238U and the activity ratio of 234U/238U ([234U/238U]AR). The results show that the 238U concentration of ice samples was less than that of the underlying water. The [234U/238U]AR of ice in the five saline lakes was similar to that of the underlying water with less than a 10‰ variation, suggesting no observable fractionation between ice and dissolved water. Thus, the ice freeze-thaw processes have almost no effect on the uranium content and [234U/238U]AR of the sampled saline lakes, which were characterized by a limited recharge volume from surface runoff, groundwater, and ice volume, namely the close saline lake in arid alpine background. The results from the indoor freeze-thaw experiments also showed that the U isotopic composition of Qinghai Lake waters and ice were similar with the 238U concentration of the ice was about 40% of that of the dissolved lake water, supporting the data obtained from natural saline lakes. The above results provide important insights into whether it is feasible to use U isotopes for absolute dating and/or paleohydrologic analysis of lake sediments or biogenic shell materials. In addition, the results are important for evaluating the [234U/238U]AR and uranium concentrations in seawater when there exists a process of melting polar ice, and for determining the initial delta 234U variations needed for dating of coral and other fossil materials.